INVESTOR REACTION ANALYSIS OF LEGISLATIVE ELECTION EVENTS APRIL 9 AND THE PRESIDENT OF THE REPUBLIC OF INDONESIA JULY 9 2014 - Oktaviana, Hilda; Adib, Noval (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of the research is to test the information content of the Legislative election on 9th April and the Presidential election of 9th July 2014. The presence or absence of information content of the event reflects the presence of market or investor reaction. The market reaction can be measured with the amount of profit, namely return and abnormal return. The research samples are taken using the method of purposive sampling, and there are 45 stock companies included in the LQ-45 index in 2014. The statistical test used by the research is T-test (Paired two Samples for Mean). The observation periods are divided into 5 and 10 days before the legislative and presidential election, and 5 and 10 days after the event. The research results show that there is an increase in the profit level which is measured with stock return 10 days after the legislative election, while in the preiod of 5 days after the legislative election, stock return remains in the same point. However, when measurement is conducted using abnormal return, the result shows that no investor gains abnormar return both 5 days and 10 days after the election. Meanwhile, stock return during the period of 5 and 10 days after the presidential election experience a decrease and there is no investor gaining abnormal return on the same period. Keywords: Legislative General Election, Presidential Election, Stock Return and Abnormal Return